Concept and Implementation: Managerial Effectiveness in the Era of Society 5.0 - Juhari; Tuha, Panca Tuah; Makrus, Mohamad; Afrizal; Suhardi (GoAcademica Research & Publishing, 2024)
Managerial Effectiveness in Society 5.0 Era is characterized by rapid changes in technology, management of big data, adaptation of work paradigms, data security, changing employee skills, stronger innovation, ethical considerations, and increasing complexity of the business environment. Managers need to develop strong leadership, adaptability, and understanding of technology and social trends. In facing this challenge, managers need to develop adaptive leadership, creativity in managing resources, and a deep understanding of the implications of technology and social trends. In this journal, we analyze the concept of the managerial effectiveness paradigm needed to face Society 5.0, explore strategies to overcome existing challenges, and identify important implications for developing effective managerial skills. Through a deep understanding of the concept and implementation of managerial effectiveness in the Society 5.0 era, this journal provides valuable insights for practitioners and researchers in facing dynamic changes in the business and social environment.